Comportamento do sono e desenvolvimento motor em crianças de 12 a 18 meses - Oliveira, Natalia Rodrigues (2015)
The health monitoring of the child in the first years of life is essential, since alterations in the neuromotor development and sleep behavior can be detected by the professionals, who ameliorate risk situations through early interventions. The aim of this study was to evaluate the sleep behavior and motor development of the 12- to 18-month-old child using the Infant Sleep Questionnaire (ISQ) and the Alberta Infant Motor Scale (AIMS). To verify the association of the sociodemographic and educational variables of the caregiver and neonates with the final scores of the Infant Sleep Questionnaire (ISQ) - Brazilian version and AIMS. This cross-sectional and quantitative study was carried out at the Pediatric Outpatient Clinic of a reference hospital in Fortaleza, CE, Brazil, and at home. Its sample is made up of 50 children and 50 caregivers, from April to October 2014. Participants were approached by direct search of medical records or contact with parents and professionals of the service; For this purpose, an instrument for the characterization of the participants, ISQ - Brazilian version and AIMS, approved by the Research Ethics Committee under protocol No. 422.103. Most caregivers are female (92%), with a mean age of 29 years and the majority between 25-34 years (50%), stable union (44%). Among females, females predominated (58%), gestational age between 35-41 weeks, born full term (84%), between 12 and 13 months of chronological age (36%), mean of 14.58 Months. The prevalence of normality (score <12) in 29 (58%) children was determined according to the final ISQ (Brazilian version), in children's sleep behavior classification. Most caregivers (62%) reported that their children had no sleep problems. There was a significant association between the final ISQ score (Brazilian version) and the criterion of the evaluator (p = 0.000). Regarding the motor development evaluation, the AIMS final scores resulted in normal (70%), suspect (20%) and atypical (10%) performance. A statistically significant association between final ISQ scores - Brazilian version with caregiver's age (p = 0.022) and Apgar scores at the fifth minute of life (p = 0.049); Final AIMS scores with gestational age (p = 0.013) and chronological age (p = 0.001). The final AIMS scores and final ISQ scores (Brazilian version) did not present statistical significance (p = 0.240). It was concluded that sleep behavior and gross motor development at the age of 12 to 18 months were not directly associated with most variables. However, it is emphasized that parental, environmental and organic factors are active determinants in this process, and this relationship with adequate sleep allows the brain activity to act in favor of development.